Axion Clouds around Neutron Stars - Dion Noordhuis; Anirudh Prabhu; Christoph Weniger; Samuel J. Witte (Physical Review X)
Recent work has shown that axions can be efficiently produced via nonstationary pair plasma discharges in the polar cap region of pulsars. Here, we point out that for axion masses 10^{−9}≲m_{a}≲10^{−4}  eV a sizable fraction of the sourced axion population will be gravitationally confined to the neutron star. These axions accumulate over astrophysical timescales, thereby forming a dense “axion cloud” around the star. We argue that the existence of such a cloud, with densities reaching and potentially exceeding O(10^{22})  GeV cm^{−3}, is a generic expectation across a wide range of parameter space. For axion masses m_{a}≳10^{-7}  eV, energy is primarily radiated from the axion cloud via resonant axion-photon mixing, generating a number of distinctive signatures that include a sharp line in the radio spectrum of each pulsar (located at the axion mass, and with an order percent-level width) and transient events arising from the reconfiguration of charge densities in the magnetosphere. While a deeper understanding of the systematic uncertainties in these systems is required, our current estimates suggest that existing radio telescopes could improve sensitivity to the axion-photon coupling by more than an order of magnitude.